Natural Products from Mediterranean Diet: From Anti-Inflammatory Agents to Dietary Epigenetic Modulators - Kontogiorgis, C.A.; Bompou, E.-M.; Ntella, M.; Berghe, W. Vanden (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2010)
Today, chronic diseases, such as cancer, obesity and type II diabetes, cardiovascular diseases, neurodegenerative diseases, and aging are replacing worldwide morbidity and mortality from infectious diseases. In addition, various links have been established between diet and a range of chronic diseases. Thus, nutrition research has shifted from focusing exclusively on alleviating nutrient deficiencies to stressing chronic diseases prevention. The Mediterranean diet, representing the dietary pattern usually consumed among the populations bordering the Mediterranean Sea, has been widely reported to be a model of healthy eating for its contribution to a favorable health status and a better quality of life. Though the healthful properties of the Mediterranean diet as a whole gained recognition, basic researchers are nowadays concentrating their efforts on individual food items, e.g. cereals, fruits, vegetable, olive oil, and their components (e.g. fibers, vitamins, polyphenols). Today there is a growing interest in the composition of manufactured functional foods with health protective properties. Inflammation is a complex stereotypical reaction of the body expressing the response to damage of its cells and vascularized tissues. A number of various mediators are implicated in this phenomenon. Essentially, inflammation involves a cellular and oxidative component. The cellular component involves the movement of leukocytes from blood vessels into the inflamed tissue. Once leukocytes arrive at sites of infection and/or inflammation, they release mediators, which control the subsequent accumulation and activation of other cells. Many enzymes, like cellular phospholipases, especially phospholipase (PLA) A and C, are activated during inflammation and degrade phospholipids to arachidonic acid (AA) as well as the enzymes implicated in the enzymatic oxidation of AA like prostaglandin synthases, cyclooxygenases (COXs) and lipoxygenases (LOXs). In addition, reactive oxygen species (ROS), including hydroxyl radicals (.OH), superoxide anion (O2 -.), hydrogen peroxide and ferric radical, mediate cell damage in a variety of pathophysiological conditions and are responsible for oxidative injury of enzymes, lipid membranes, and DNA in living cells and tissues. Nitric oxide (NO) also plays a role as an effector in inflammation. Natural agents have been ethnomedically used for thousands of years for the treatment of several pathologies and have mostly proven to be safe. Recently, in vivo and in vitro studies showed potential anti-inflammatory role for some of the existing natural agents. Indeed, results from cross-sectional studies and feeding trials in Mediterranean populations suggest that the Med-Diet has beneficial anti-inflammatory effects. The recent observation that dietary compounds can epigenetically reprogram gene expression via DNA methylation changes has important implications for cancer prevention and chronic inflammatory disease. In a broader context, there is growing interest in dietary modulators of DNA methyltransferases, histone deacetylases (HDAC), and sirtuin (SIRT) deacetylases and their impact on epigenetic inflammatory mechanisms affecting health and disease. This review provides an overview of the literature related to the anti-inflammatory effects of some of the natural products included in Mediterranean diet which have potential value in the treatment of inflammatory diseases.
Keywords: Natural products